Kontribusi Disiplin, Kompetensi dan Pelatihan Kerja terhadap Kinerja melalui Motivasi Kerja Anggota pada Densus 88 Anti Teror POLRI - Wakum, Ira Yuliana; B, Hamsinah; Mukrodi, Mukrodi; Sudaryana, Yayan; Sugiarti, Endang (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the effects of discipline, competence, and job training on work motivation and performance among members of Densus 88 Anti-Terror of the Indonesian National Police, as well as to analyze the role of work motivation in influencing performance. The research employs a quantitative approach with descriptive and associative methods, involving 268 respondents selected through probability sampling from a total population of 808 members. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results indicate that discipline and job training have a positive and significant effect on work motivation, while competence does not have a significant effect. Furthermore, discipline, competence, job training, and work motivation were found to have positive and significant effects on members’ performance. These findings highlight the importance of job training and discipline as key factors in fostering motivation and improving performance, and suggest that competence is more effective when directly linked to performance achievement. This research contributes to strengthening human resource management strategies within the police force, particularly in anti-terror task units.